Do the Perceived Effects of Injecting Insulin Influence Adherence to Insulin Regimens in Adolescents with Type 1 Diabetes Mellitus (T1DM)? - Diprose, Sheryl (2009)
Aim: This study aimed to investigate the perceived effects of injecting insulin in adolescents with Type One Diabetes Mellitus (T1DM) and the resulting implications of these to their insulin regimens. Background: Self injections of insulin play a huge part in the life of individuals with T1DM and research has shown that there are both physical and psychological problems associated with injecting insulin. These effects associated with administering insulin injections could contribute towards adolescent’s reasons for not adhering to their insulin regimen and thus, lead to long term complications. Methods: This study took a quantitative approach by administering a questionnaire, adapted from the third version of the Diabetes Attitude Questionnaire developed in 1998. Over a 2 month period all adolescents, using the definition of young people aged between 10 and 19 years (World Health Organisation, 1995), attending a paediatric diabetes clinic in a large teaching hospital in the East Midlands were approached to participate in this study. Results: This study has found that there is a small negative correlation between adolescent’s attitudes towards diabetes and adherence to insulin regimens, so as the number of injections missed each day increases, the adolescent’s attitudes towards diabetes become more negative. The results also show that although by looking at the graphs of the results there appears to be a difference in the number of males and females who missed injections, when the data was analysed using a Mann-Whitney U test, no significant difference was found. Conclusions: The results of this research are not conclusive. Further research such as a larger version of this study may provide more distinguishable results enabling the alternative hypothesis to be either accepted or rejected.